Surveillance Function in Law Enforcement in Indonesia: Integrated Criminal Justice System Perspective - Ni Nengah Adiyaryani; Kadek Agus Sudiarawan (University of Udayana, 2021)
This study aims to determine the role of law enforcement officer in integrated criminal justice system and to find the concept of surveillance patterns that need to be established for law enforcement officer for the future integrated criminal justice system (ius constituendum). This is normative legal research using a statutory approach and a conceptual approach. Analysis using qualitative methods and the results are presented in descriptive analysis report. The results show that the integrated criminal justice system did not have an integrated surveillance system in a special form that was implemented by the law enforcement officers and its society yet. It still applying an internal and conventional surveillance pattern. Hence, empowering the existing surveillance pattern and creating an integrated surveillance pattern could be a solution to overcome the weakness of the surveillance system in the Integrated Criminal Justice System nowadays which caused by the fragmented surveillance system without any external-cross institutional surveillance.